Implementation of Multicultural Education Through Introduction to Baduy Culture in Increasing Learning Motivation in Elementary Schools - Sastra Wijaya; Arifin Maksum; Nina Nurhasanah (Institute of Computer Science (IOCS), 2022)
This study aims to find out about the implementation of multicultural education in elementary schools through the introduction of Baduy culture and its influence on increasing student learning motivation. The research was conducted at Rocek 3 Public Elementary School, Pandeglang Regency, Banten Province, with 30 grade IV students as the subject of research. The research focused on social science subjects. This research was conducted using descriptive qualitative research methods, using collection techniques through test questions, observation, and interviews. The results of the research on the calculation of the mean, median, and mode are 0.50 so it does not reveal the slope of the curve which indicates a tendency for positive results in the data. Calculations according to the R-Square value show that there is an influence rate between variables of 82.3%, this has met the requirements for the relationship between variables through a hypothesis number above 50% which means good. The results of the calculation on the homogeneity test show the numbers on Sig. 0.003 ? ? (0.05), while the significance value (2-tailed) on the introduction of Baduy culture in the implementation of multicultural education on student learning motivation in elementary schools is 0.003 ? 0.05, thus accepting Ha and rejecting H0. It can be concluded that there is a significant influence on learning motivation and introduction to Baduy culture variables in the implementation of multicultural education.